A document analysis of the visibility of sustainability in TVE teacher education programme: the case of a Malaysian HEI - Chinedu, C. C; Wan Mohamed, Wan Azlinda (Universiti Putra Malaysia Press, 2017)
There has been a global call for institutions of learning to engage in Education for Sustainable Development (ESD) by leading world organisations. Although scholars advocate for an interdisciplinary approach to sustainability, the research literature shows that majority of sustainability issues are addressed through fields such as environmental and developmental education. There has also been a call for the integration of Sustainable Development (SD) in Technical and Vocational Education and Training (TVET) programmes by various scholars and bodies such as the United Nations Education, Scientific and Cultural Organisation (UNESCO). The issue, however, is that Technical and Vocational Education (TVE) programmes are not yet embracing this call to integrate ESD into their programmes. Hence, it is imperative to reiterate the intersection between TVE and SD and how the former can contribute significantly to the SD agenda. Therefore, by completing a qualitative documentary analysis of a TVE programme, using a Malaysian Higher Education Institution (HEI) as a case study, this paper discusses the visibility of sustainability in TVE programmes as well as explores the overarching goal of ESD and why it is especially crucial for TVE. Findings reveal that the concept of sustainability is only barely reflected in the TVE teacher training curriculum. Recommendations for practice change and further research are presented and discussed.